Antibacterial Evaluation and Phytochemical Screening of eucalyptus gomphocephala DC against Pseudomonas aeruginosa - Bouharb, Hayate; El Badaoui, Khalid; Zair, Touriya; Shisseh, Hafsa; Chakir, Said; Alaoui, Tajelmolk (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â  Â Objective: The aim was to evaluate the in vitro antibacterial activities of essential oil and extracts from Eucalyptus gomphocephala leaf on the growth of six strains of Pseudomonas aeruginosa. Methods: Aqueous, ethanol, hexane, petroleum ether extracts and essential oil of E. gomphocephala leaf were investigated on six strains of P. aeruginosa. The antibacterial activity was determined by agar-well diffusion method and expressed as the average diameter of the zone of inhibition of bacterial growth around the wells. The minimum inhibitory concentration (MIC) of active extracts was determined by microdilution assay. The preliminary phytochemical screening of the leaf was conducted using various standard methods. Results: The present study reveals that the essential oil does not show any activity against all strains. Extracts showed varying degrees of inhibition on the tested microorganisms. The petroleum ether and ethanol had a lower activity against strains. However, aqueous and hexane leaf extracts, of E. gomphocephala presented the highest anti P. aeruginosa activity against all strains tested. The MIC and minimum bactericidal concentration of the aqueous and hexane extracts ranged between 6.25 and 50 mg/ml. Qualitative analysis of E. gomphocephala revealed the presence of biological active compounds such as tannins, flavonoids, saponins and steroids/triterpenes. Conclusion: To conclude, extracts of E. gomphocephala leaf may be pursued as an antibacterial agent for the treatment of infections caused by P. aeruginosa. Keywords: Eucalyptus gomphocephala, Extracts, Antibacterial activity, Pseudomonas aeruginosa, Phytochemical screening